Characteristics of Psychological Sphere of Pupils of Secondary School Age - Viktoriya Kyrychenko (Lesya Ukrainka Volyn National University, 2015)
In the article the author analyses the main aspects concerning peculiarity of psychological development of teenagers. The author stresses out the peculiarities of psychological sphere of teenagers and influence of practicing physical culture and sport on intellectual and physical development of pupils of a secondary school.